2016
DOI: 10.1142/s0218271816500310
|View full text |Cite
|
Sign up to set email alerts
|

The van der Waals fluid and its role in cosmology

Abstract: We analyze the properties of a generic cosmological fluid described by the van der Waals equation of state. Exact solutions for the energy density evolution are found as implicit functions of the scale factor for a flat Friedmann-Robertson-Walker space-time. The possible values of the free parameter in the van der Waals equation are selected a posteriori, in accordance with asymptotic behaviors that are physically relevant. The stability of the model against small perturbations is studied through the hydrodyna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Combining this energy definition with the thermodynamic pressure definition and the Friedmann second equation, we got the p(V ) relation. Bearing the Friedmann first equation in mind, we could obtain the p(ρ) relation, and showed that the obtained solutions can be used to model the universe expansion, a result which is in agreement with some previous attempts [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. We also found out that some type of the obtained solutions may be used to unify the dominated fluids in both the primary inflationary and current accelerating phases into one model.…”
Section: Summary and Discussionsupporting
confidence: 88%
“…Combining this energy definition with the thermodynamic pressure definition and the Friedmann second equation, we got the p(V ) relation. Bearing the Friedmann first equation in mind, we could obtain the p(ρ) relation, and showed that the obtained solutions can be used to model the universe expansion, a result which is in agreement with some previous attempts [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. We also found out that some type of the obtained solutions may be used to unify the dominated fluids in both the primary inflationary and current accelerating phases into one model.…”
Section: Summary and Discussionsupporting
confidence: 88%
“…It is efficient to discuss the conditions for quintom phases [54] to provide inflationary phase transition. This continuity established with the modification of these parameters result into multi-parameter Van-Der-Waals like EOSs [1][2][3][4][5][6][7][8][9][10]. The EOS parameter can provide the necessary conditions for inflation as well as radiation dominated universe, dark matter dominated universe but it fails to discuss the conditions of decelerating phase (after inflation), graceful exit and the reheating phase [1].…”
Section: Signification Of These Three Different Modelsmentioning
confidence: 99%
“…Non-linearity in the fluid of cosmology is nothing but the modification of equation of state with higher order correction [1][2][3][4][5]. This correction might provide the solution of the negative pressure problem, late time acceleration and cosmic acceleration problems [6,8].…”
mentioning
confidence: 99%
“…Consider now the case of filling the Universe by real gas consisting of molecules and described by the Van der Waals equation of state. (Another version of the description of non-ideal dark matter is given in articles [12][13][14][15].) If the temperature is measured in degrees, then, according to [16], it takes on the form…”
Section: Issn 1991-346xmentioning
confidence: 99%